2010
DOI: 10.1021/cm100536a
|View full text |Cite
|
Sign up to set email alerts
|

Role of Li2B12H12 for the Formation and Decomposition of LiBH4

Abstract: By in situ X-ray diffraction (XRD) and nuclear magnetic resonance (NMR) spectroscopy, the role of Li2B12H12 for the sorption of LiBH4 is analyzed. We demonstrate that Li2B12H12 and an amorphous Li2B10H10 phase are formed by the reaction of LiBH4 with diborane (B2H6) at 200 °C. Based on our present results, we propose that the Li2B12H12 formation in the desorption of LiBH4 can be explained as a result of reaction of diborane and LiBH4. This reaction of the borohydride with diborane may also be observed for othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
142
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 30 publications
8
142
0
Order By: Relevance
“…4) . [39,47] We also found that the back pressure of the reacting system affects the yield of Na 2 B 12 H 12 . In a closed system, the yield of Na 2 B 12 H 12 is improved (~10 %, based upon NaB 3 H 8 ), which indicates a more efficient reaction between the volatile boranes and the solid products forming Na 2 B 12 H 12 .…”
Section: Synthesis Of Na 2 B 12 H 12mentioning
confidence: 71%
“…4) . [39,47] We also found that the back pressure of the reacting system affects the yield of Na 2 B 12 H 12 . In a closed system, the yield of Na 2 B 12 H 12 is improved (~10 %, based upon NaB 3 H 8 ), which indicates a more efficient reaction between the volatile boranes and the solid products forming Na 2 B 12 H 12 .…”
Section: Synthesis Of Na 2 B 12 H 12mentioning
confidence: 71%
“…This experimental line broadening was compared with second moment calculations. The expected dipolar broadening of 11 B with its surrounding nuclei, 11 B, 10 B, 1 H, 6 Li, and 7 Li, in the case of a rigid lattice is expected to be 47.2 kHz. This is much broader than the experimental line Li single pulse excitation spectra of 30 wt % LiBH 4 in ordered porous silica (MCM-41) for different temperatures with and without 1 H decoupling.…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…The formation mechanism of Na2B12H12 is not yet clear; the borohydride may originate from the reaction of boranes with unreacted NaBH4, which was proposed by the first principles calculations [25]. In fact, a similar decomposition route was proposed for LiBH4, where Friedrichs et al [30] suggested that the formation of Li2B12H12 arises from the reaction of the borane evolving from LiBH4 with the remaining starting material. First principles calculations suggest that Na2B12H12 has significant ionic character and is relatively stable and if it was formed during the thermal decomposition of NaBH4, thermodynamically one would not expect its existence to be fleeting [31].…”
Section: Thermal Decompositionmentioning
confidence: 99%